Examining the Impact of Influencers and Bloggers on Behavioral Intentions among Youth in Sindh Pakistan - Junejo, Ikramuddin; Memon, Abeer; Saraih, Ummi Naiemah; Akhund, Zuha; Shah, Mahnoor; Zahari, Mohd Khairulnizam (Journal of Communication in Scientific Inquiry (JCSI), 2024)
This study examines the impact of attitude, social media influencers, electronic word of mouth (e-WOM) and credibility on behavioral intention among youth. An online survey was distributed with the help of an adapted questionnaire from past studies. A total of 200 cases were considered in this study, and reliability analysis and regression analysis were performed in SPSS version 25. The findings revealed that all variables of attitude, social media influencers, and electronic word of mouth (e-WOM) positively and significantly impact behavioral intention. However, the attitude was found to have a more significant impact on the behavior of the youth of Pakistan due to higher beta values than the dependent variables. Therefore, policymakers in the textile industry can consider these variables in the future.